Generic histories of German cinema : genre and its deviations - Fisher, Jaimey (Rochester, New York : Camden House, 2013)
"Generic Histories offers a fresh approach, tracing a series of key genres -- including horror, science fiction, the thriller, Heimat films, and war films -- over the course of German cinema history. It also addresses detective films, comedies, policiers, and romances that deliberately localize global genres within Germany - a form of transnationalism frequently neglected. This focus on genre and history encourages rethinking of the traditional opposition (and hierarchy) between art and popular cinema that has informed German film studies. In these ways, the volume foregrounds genre theory's potential for rethinking film history as well as cultural history more broadly."--Publisher's description.
Introduction: toward generic histories: film genre, genre theory, and German film studies / Jaimey Fisher -- Parallel modernities: from haunted screen to universal horror / Gerd Gemunden -- The essay film and its German variations / Nora M. Alter -- The limits of futurity: German science fiction film in the course of time / Lutz Koepnick -- The situation is hopeless, but not desperate: UFA's early sound film musicals / Eric Rentschler -- Resisting the war (film): Wicki's "masterpiece" Die Brucke (1959) and its generic transformations / Jaimey Fisher -- Ironizing identity: the German crime genre and the Edgar Wallace production trend of the 1960s / Sascha Gerhards -- From Siodmak to Schlingensief: the return of history as horror / Kris Vander Lugt -- Producing adaptations: Bernd Eichinger, Christiane F., and German film history / Hester Baer -- Exceptional thrills: genrification, Dr. Mabuse, and Das Experiment / Steve Choe -- The Heimat film in the twenty-first century: negotiating the New German cinema to return to Papas Kino / Paul Cooke -- The romantic comedy and its other: representations of romance in German cinema since 1990 / Antje Ascheid -- Yearning for genre: the films of Dominik Graf / Marco Abel.
Includes bibliographical references (pages 285-300) and index.
Print version record.
English.
JSTOR
Keywords: Motion pictures -- Germany -- History and criticism; Film genres -- Germany; Cinéma -- Allemagne -- Histoire et critique; Genres cinématographiques -- Allemagne; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Film genres; Motion pictures; Germany; Criticism, interpretation, etc